ASUHAN KEBIDANAN PERSALINAN KALA I PADA NY.A DENGAN TEKNIK RELAKSASI MASASE EFFLEURAGE DI KLINIK PRATAMA MARKO KECAMATAN MEDAN JOHOR TAHUN 2020 - Kristina Natalia Sidabalok; Nur Alvi Sayhrin; Dina Junita Br Katare; Rifa Lumban Gaol; Lusiana Andika Situmorang; Malinda Bahra (Pusat Riset dan Inovasi Nasional, 2022)
The MDG`s national target is to reduce the maternal mortality rate by three quarters from the maternal mortality rate in 1990 of 405 per 100,000 live births to 102 per 100,000 live births in 2015. World Health Organization (WHO) Maternal Mortality Rate (MMR) in the world that is, 289,000 people, and estimates that 800 women die each day due to complications of pregnancy and childbirth. Approximately 99% of all maternal deaths occur in developing countries, about 80% of maternal deaths are the result of increased complications during pregnancy, childbirth and after delivery. The Health Profile of North Sumatra Province in 2016 states that the coverage of deliveries assisted by health workers shows an increasing trend, namely from 86.73% in 2010 to 90.05% in 2016, even the achievement in 2016 was the highest achievement in terms of delivery assistance by health worker in 7 years Effleurage technique is a massage technique using the palms of the hands in a circular motion pattern on the lower part of the waist. Massase effleurage technique can reduce labor pain during the first stage of the active phase if it is done correctly, which is done every time there is a contraction and done for about 20 minutes. The general objective of this study was to provide midwifery care for the first stage of labor to Mrs. A with the Effleurage Massage Relaxation Technique at the Pratama Marko clinic using Helen Varney's 7 steps midwifery management. In making this report the authors use descriptive methods with a case study model. The results showed that the respondent Ny. A 28 years old during the first stage of labor with massage relaxation technique at effleurage at the Pratama Clinic, Jl. Floodgate IV kec. Medan Johor.